1974
DOI: 10.1002/cjce.5450520314
|View full text |Cite
|
Sign up to set email alerts
|

Water activity data representation of aqueous solutions at 25°C

Abstract: Polynomial expressions have been fitted to the complete range of available water‐activity data for 396 electrolyte and non‐electrolyte aqueous binary systems. The standard deviation of regression rarely exceeded 0.001 and was less than 0.0002 in most cases. Such data representation is useful for the prediction of the water‐activity of mixed moderately concentrated aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…3, which follows the order of MgSO 4 N KCl N NaCl N MgCl 2 at the concentrations higher than 1.0 mol/L. It can be observed that the predicted values are in good agreement with experimental data measured by Teng and Lenzi [22] in the concentration range in question. Interestingly, MgCl 2 shows a distinct difference compared to NaCl, KCl and MgSO 4 .…”
Section: Vapor Pressure Depressionsupporting
confidence: 87%
“…3, which follows the order of MgSO 4 N KCl N NaCl N MgCl 2 at the concentrations higher than 1.0 mol/L. It can be observed that the predicted values are in good agreement with experimental data measured by Teng and Lenzi [22] in the concentration range in question. Interestingly, MgCl 2 shows a distinct difference compared to NaCl, KCl and MgSO 4 .…”
Section: Vapor Pressure Depressionsupporting
confidence: 87%
“…a predicted using the literature's K value; b predicted using the K value calculated from all experimental data. Experimental data: empty circles, Scatchard et al (1938); filled diamonds, Teng and Lenzi (1974); filled triangles, Bubnik et al (1995) very good up to about 60% concentration; however, above this value, deviations were quite important. Predictions made using K values calculated from experimental data from low to high concentrations were not sufficient to improve modeling of data for the whole curve.…”
Section: Resultsmentioning
confidence: 93%
“…a Predicted using the literature's value of K; b predicted using the K value calculated from all experimental data. Experimental data: x symbol, Teng and Lenzi (1974); filled triangles, Comesaña et al (2001); filled diamonds, Ninni et al (2000); empty circles, Peng et al (2001) Fructose, 25°C Fig. 2 a Comparison of predicted and experimental a w data for fructose solutions at 25°C.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In these cases, the activity of the solvent can be evaluated directly from the corresponding solution vapour pressure and thus the experimental dependence of the solvent activity on composition a 1 (m 2 , m 3 ) is obtained. To describe these systems, binary or ternary, it is usual to employ polynomial expressions [1][2][3][4][5][6][7][8][9][10][11], which are used independently of the nature of the solution. The problem is that the first terms of the polynomial are strongly dependent on the nature of the system and consequently, in most cases these expressions are not thermodynamically consistent, as they do not satisfy the limiting behavior required by the Thermodynamics of solutions.…”
Section: Introductionmentioning
confidence: 99%